Energy harvesting from asphalt pavement using thermoelectric technology. (1st November 2017) - Jiang, Wei; Yuan, Dongdong; Xu, Shudong; Hu, Huitao; Xiao, Jingjing; Sha, Aimin; Huang, Yue
Highlights: A brand new set of road thermoelectric generator system was developed. Road temperature gradient and characteristics in different seasons were tested. Electric outputs of road thermoelectric generator system were tested outdoor. Relationship between output voltage and temperature difference was obtained. Abstract: Nowadays, energy harvesting from road has become a research hotspot. The power generation system within asphalt pavement based on thermoelectric technology was studied in this paper. The characteristics of temperature difference between the pavement and ambient air, as well as the temperature gradient within road surface were investigated by collecting data on-site in different seasons. Based on this, a novel set of road thermoelectric generator system (RTEGS) was developed, which can generate electricity when there is a temperature difference between road surface and ambient air. In addition, a RTEGS prototype was fabricated to verify the energy generation capacity based on indoor and outdoor tests. Results showed that the output voltage of RTEGS was about 0.4 V by asphalt mixture slab (300 mm × 300 mm by size), when the temperature difference between road surface and ambient air was 15 °C in winter. While in summer, the output voltage was about 0.6–0.7 V, with a temperature difference of 25–30 °C. This means that some 160 kW h of energy can be obtained in 8 h from a road of 1 km in length and 10 m in width. For asphalt pavement in tropical and subtropical regions, the large temperature difference would be more suitable for RTEGS. The findings and research experiments from this study will provide a good starting point and reference for the development and application of pavement thermoelectric technology.